Remembrances of Rashid: life-histories as lessons in the Deoband movement - Jones, J (Cambridge University Press, 2023)
The tazkira, a long-established genre of life-history writing in South Asian literature, was increasingly used over the course of the twentieth century to document the lives and achievements of ‘ulamā (‘learned men’, or scholars of religion). This paper explores a foundational work within this genre: ‘Ashīq Ilahī Mīrutī’s Tazkira’t al-Rashīd (first published 1908-1910), a life-history of the Dēōbandī scholar and Sūfī shāykh Rashīd Ahmad Gangōhī. It argues that such life-histories of ‘ulamā were written not merely as historical records but as ‘lessons’ to their readers. This paper illustrates how the tazkira appropriated Gangōhī’s life and teachings to provide an indispensable repository of Dēōbandī understanding on issues such as tarīqah (the Sūfī path), sharī‘ah (religious law), pīrī-murīdī (the master-disciple relationship), religious and social conduct and relations with the state. The paper thus makes a case for understanding the tazkira as an important vehicle for informing and shaping the religious behaviour of a Muslim public, which was employed ultimately by both the Dēōbandī and other Islamic revivalist movements.